AL-BĀQILLĀNĪ'S COSMOLOGICAL ARGUMENT FROM AGENCY. Issue 2 (5th August 2016) - Muhtaroglu, Nazif
Abstract: In this paper, I propose to expose the logical structure al-Bāqillānī's argument for the existence of God and argue that it presents a distinctive type of argument that cannot be classified under the classical types of ontological, cosmological, and design arguments. The peculiarity of al-Bāqillānī's argument is related to the concept of God it presupposes. Developing Herbert Davidson's insights regarding this argument and criticizing Majid Fakhry's interpretation of it, I aim to clarify this concept of God by the concept of agency. In a nutshell, I argue that al-Bāqillānī presents a distinctive type of argument for the existence of God, which I propose calling the "cosmological argument from agency." I consider it cosmological because it is an inference from the universe to the existence of God. Nonetheless, it is different from the classical versions of the cosmological argument for that the concept of agency and the idea of a personal deity play a central role in this argument. Résumé: Dans cet article, je propose d'explorer la structure logique de l'argument d'al-Bāqillānī en faveur de l'existence de Dieu et de montrer en quoi cet argument ne peut être rangé au sein de la classification classique des arguments de type ontologique, cosmologique et de dessein. La particularité de l'argument d'al-Bāqillānī réside dans le concept de Dieu qu'il présuppose. En me servant de l'analyse de Herbert Davidson et en critiquant l'interprétation de cet argument par Majid Fakhry, j'espère clarifier ce concept de Dieu par le concept d'agent. Pour résumer, je tente de démontrer qu'al-Bāqillānī présente un type d'argument particulier que nous appellerons "l'argument cosmologique à partir de l'agent". Je le considère cosmologique parce qu'il s'agit d'une inférence qui part de l'univers pour aboutir à l'existence de Dieu. Néanmoins, cet argument est différent de l'argument cosmologique classique car il laisse une plus grande place au concept d'agent ainsi qu'à l'idée d'un dieu personnel.